Proteomic studies on patient responses to chemotherapy, radiotherapy and immunotherapy in cancers - Duarte, Jessica Da Gama (Division of Medical Biochemistry, 2016)
There is increasing evidence that the aberrant expression of cancer-testis (CT) antigens - a family of ca. 150 proteins that are both autoimmunogenic and mainly restricted to tumours in various types of human cancers - makes them attractive immunotherapy targets, as well as possible cancer diagnostic markers. We carried out a retrospective serological study of primary and secondary autoimmune responses of various cohorts of cancer patients prior to and/or following a variety of distinct treatments (chemotherapy, radiotherapy and immunotherapy), using a large number of archived human serum samples. Our goals were to develop and validate a novel cancer-testis and -associated antigen microarray platform and to then explore its utility and general applicability in the cancer immunology field. In addition, we sought to cross-correlate our protein microarray data from specific cohorts with in vitro T-cell re-stimulation assays for a selected subset of patients. Furthermore, as a means of determining the biological significance of our protein microarray data, we also collected clinical patient data where possible. The underlying hypothesis of our study was that there were measurable differences in autoantibody repertoires towards tumour-specific and -associated antigens between pre- and post-treated cancer patient samples (using various trial therapies), potentially augmented by prior chemo- or radiotherapy, which would correlate with likelihood of response of individual patients to a given therapeutic treatment - including those treatments that aim to generate T-cell responses - and which would also correlate with the nature and extent of individual patient responses to treatment.